Islamic international law : historical foundations and al-Shaybani's Siyar - Bashir, Khaled Ramadan (Edward Elgar Publishing, 2018)
Through the analysis of Al-Shaybani's most prolific work As-Siyar Al Kabier, this book offers a unique insight into the classic Islamic perspective on international law. Despite being recognised as one of the earliest contributors to the field of international law, there has been little written, in English, on Al-Shaybani's work. This book will go some way towards filling the lacuna. Islamic International Law examines Al-Shaybani's work alongside that of other leading scholars such as Augustine, Gratian, Aquinas, Vitoria and Grotius, proving a full picture of early thinking on international law. Individual chapters provide discussion on Al-Shaybani's writing in relation to war, peace, the consequences of war and diplomatic missions. Khaled Ramadan Bashir uses contemporary international law vocabulary to enable the reader to consider Al-Shaybani's writing in a modern context. This book will be a useful and unique resource for scholars in the field of International Islamic law, bringing together and translating a number of historical sources to form one accessible and coherent text. Scholars researching the historical and jurisprudential origins of public international law topics, such as international humanitarian law, just war, international dispute resolution, asylum and diplomacy will also find the book to be an interesting and valuable text.